The reflection of the method of self assessment on tax revenues :Applied case study in the General Tax Authority (Entrepreneurship Journal for Finance and Business, 2023)
A case study of self-assessment and tax revenues An applied case study of the method of self-assessment of income in the General Tax Authority - Companies Department, and the problem of an overview of assessment and tax revenues was presented, and the study reached the stage of assessment and public revenues, and the study reached the stage of self-assessment and study, self-drawing and study in Abroad, Self-Painting and Study Abroad. Its final accounts through various activities, and that the mutual trust between the two parties to the tax accounting process) plays a key role in this type of income estimation methods, and the research came out with a variety of combination of relationships and mutual trust between the two parties to the tax accounting process through the development of tax awareness of the citizen. The one who successfully triggered the application of this method of estimating income, taking into account the tax administration’s commitment to the tax law and striving instructions not to be unfair to the taxpayer when estimating his income.